Digital libraries : the era of big data and data science : 16th Italian Research Conference on Digital Libraries, IRCDL 2020, Bari, Italy, January 30-31, 2020, Proceedings /: the era of big data and data science : 16th Italian Research Conference on Digital Libraries, IRCDL 2020, Bari, Italy, January 30-31, 2020, Proceedings. (2020) - Unknown
No abstract available